Calificación ante cargas dinámicas de una conexión entre una columna de guadua angustifolia y su cimentación (2013)
In this work we studied the behavior against horizontal forces of a connection between a column of Guadua Angustifolia Kunth and a foundation pedestal in reinforced concrete. Threaded rod bolts, both transverse and longitudinal, filling mortar and bands made with metal ribbons were used. Seven configurations were tested by varying the combination of the components of the connection in order to evaluate their influence on the structural response. For each configuration four specimens were built that were taken to the fault, one of them with monotonic loads and three with cyclic loads. It was found that the use of longitudinal bolts and mortar reduces both the strength and the ductility of the connection. Although the mortar filling improves the rigidity, it causes the connection failure to be fragile, which can be controlled if confinement ties are used.